What has change management in industry got to do with improving patient safety?. Issue 1027 (25th March 2011) - Noble, Douglas J; Lemer, Claire; Stanton, Emma
Abstract : Background: Healthcare is often in a constant state of change - for political, technological, patient related, and scientific reasons. Yet, for a business where change is the norm, too little time is spent thinking theoretically about how change occurs. One area where change is still needed is in patient safety. Methods: Presented is an analysis of the literature on change to suggest how this may inform patient safety. Results: No one change approach guarantees success in patient safety. Success very much depends on selecting the best fit change framework and adapting it to local context. Well regarded change models, like that of Kotter, are not well tested within a healthcare context. Those that are, such as Pettigrew, do not specifically address all the issues associated with patient safety. Kotter's phases of change may be applied in a healthcare context to enhance patient safety. Conclusion: Kotter's model is well studied in non-healthcare contexts and has potential to be adapted for improving patient safety.